A distant finish line for women: gender and the sports press in Portugal (1996-2016) - Pedro Saraiva; Virgínia Ferreira; Maria João Silveirinha (Ex Aequo: Revista da Associação Portuguesa de Estudos sobre as Mulheres)
In this paper we examine the overall evolution of the coverage of women’s sports by the three Portuguese daily sports newspapers (A Bola, O Jogo and Record), as well as the potential sexual objectification of female athletes. To this end, we conducted an analysis of the news and photographs published by these three daily newspapers over a period of 20 years (1996-2016), based on a random sample. A total of 2,414 news items, including 1,207 articles and 1,207 photographs, were collected from 186 different newspaper editions. The results do not show significant changes in the coverage of women’s sports nor a significant decrease in the sexualization of athletes, as signs of sexual objectification remain. The research suggests that policy makers should take active measures to promote equality between women and men in sports journalism.